Introductory analysis of factors affecting intercultural couples in the context of Malaysia - Wan Ahmad Fauzi, Wan Husain; Suraiya, Ibrahim; Wan Sallha, Yusoff; Intan Maizura, Abd Rashid; Irza Hanie, Abu Samah (AIP Publishing, 2021)
A study of communication processes forms inside intercultural marriages will profit numerous people, especially couples who are occupied with such connections. At the point when people find out about other people who experience comparative impediments or conditions, they can re-examine their own circumstance with a progressively exact focal point. Commonly, this changed perspective produces development in the person who is looking for answers and frequently impacts this present individual's life partner. An investigation of this sort additionally adds to the field of advising. The psychological wellness field is persistently extending and looking for extra understanding and learning about human behaviour. Humans are perplexing animals, in this manner, visit perceptions and academic examinations are important for improved cognizance. Pre-marriage, conjugal, and family mentors benefit from an investigation of intercultural relational unions as all social orders depend on relational unions and familial relationships. These relationships determine the health of a society.